RANCANG BANGUN ALAT DISTILASI PEMURNIAN BIOETANOL GRADE TEKNIS BERSKALA UKM : KAJIAN KINERJA ALAT TENTANG DERAJAD PEMURNIANNYA - Hargono Hargono; Nugraha Bayu Samodra; Nadia Zahrotul Firdausi; Agnes Kinanthi Nugraheni; Lazuardy R. Zakaria (TEKNIK, 2013)
The technical grade bioethanol can be manufactured by using distillation process at small and medium enterprises. In this research, bioethanol was made from fermentation of  rubber cassava starch (Manihot glaziovii) and gadung starch (Dioscorea hispida). From this fermentation process, 3-8% crude ethanol was produced. To achieve the objective 2-stage distillation units were designed to purify the crude ethanol product. Bioethanol produced from 1st and 2nd distillation units were of 35 and 94% purity respectively corresponding to the technical specifications desired. The design of 2-stage distillation units has been completed, included the shape and dimensions of the units, i.e. the main condenser, cylindrical in shaped, dimensions of diameter was 32cm and height was 45cm, cylindrical in shape  feeder tank/boiler, small scale volume of 5L, which can be scaled up to 65L. At 2nd distillation column, the diameter was 9cm and length was 121cm. The column was isolated using ori type bamboo filled with glasswool as isolator. The columns were filled with ceramic or glass type packing inside. The columns were equipped with thermometer to measure the temperature of ethanol-water vapor. Key words: crude bioethanol, design of 2-stage distillation, technical grade bioethanol